2007
DOI: 10.1590/s1806-37132007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de dispnéia e possíveis mecanismos fisiopatológicos envolvidos em indivíduos com obesidade graus 2 e 3

Abstract: Dyspnea is a common complaint in individuals with class II or III obesity. Such individuals present a pronounced reduction in expiratory reserve volume and an increase in the alveolar-arterial oxygen gradient. The correlations found suggest that obese individuals present dysfunction of the lower airways, and that obesity itself plays a role in the genesis of dyspnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
0
21
0
10
Order By: Relevance
“…Therefore, the real contribution of obesity to respiratory muscle strength as an independent variable could not be evaluated and interpreted, 23 making the behavior of respiratory muscle strength in obesity inconclusive and controversial. [4][5][6] In this study, the variables age and height showed no correlations with the maximum respiratory pressures; thus, they were not included in the linear regression model. This may have been due to the homogeneity of the groups with regard to these variables, unlike in the studies of Black and Hyatt, 10 Neder et al, 11 , Costa et al, 12 and Simões et al, 13 in which these variables showed a negative predictive importance for maximum respiratory pressures.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the real contribution of obesity to respiratory muscle strength as an independent variable could not be evaluated and interpreted, 23 making the behavior of respiratory muscle strength in obesity inconclusive and controversial. [4][5][6] In this study, the variables age and height showed no correlations with the maximum respiratory pressures; thus, they were not included in the linear regression model. This may have been due to the homogeneity of the groups with regard to these variables, unlike in the studies of Black and Hyatt, 10 Neder et al, 11 , Costa et al, 12 and Simões et al, 13 in which these variables showed a negative predictive importance for maximum respiratory pressures.…”
Section: Discussionmentioning
confidence: 94%
“…3 However, no consensus has been reached in the literature concerning the behavior of the respiratory muscles in the presence of increased body mass index (BMI). [4][5][6] According to Magnani and Cataneo, 5 individuals with obesity have respiratory muscle dysfunction due to changes in the relationship between the lung, chest wall, and diaphragm muscle, which in turn alter respiratory mechanics and gas exchange. It is believed that these changes cause overload in the respiratory muscles, increasing the mechanical work involved in respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Do mesmo modo, a força da musculatura respiratória representada pelas pressões inspiratória (PImax) e expiratória Fisioter Mov. 2011 jan/mar;24(1):13-21 Tabela 3 -Apresentação da média, do desvio-padrão (DP) e do valor mínimo e máximo para as variáveis após a realização do programa de reabilitação pulmonar em mulheres obesas (n = 20) na cidade de Natal, RN expiratória e da capacidade residual funcional (8,10), diminuição da complacência pulmonar e torácica, redução da força dos músculos respiratórios e distúr-bios da função pulmonar e da capacidade de exercício (21), o que fica bem evidenciado no presente estudo pelos dados obtidos para o período pré-programa de reabilitação pulmonar. Nos resultados observados neste estudo, a mudança do padrão respiratório costal para o diafragmático foi favorecida pela reabilitação pulmonar,…”
Section: Resultsunclassified
“…These findings are consistent with the strong correlation between WC and risk factors for associated diseases described in the literature. 1,2,8,31 Muscles of obese individuals have specific histological and metabolic characteristics, showing an increase in lean mass and a more powerful muscle contraction. Due to daily physical efforts to move the body and attempts of the musculoskeletal structure to maintain the body in the upright position, obese individuals have a higher proportion of skeletal muscle mass and type II fibers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,8 In addition to these diseases, other studies show that obesity can also promote considerable changes in respiratory function: decreased functional residual capacity (FRC), tidal volume (TV), and lung compliance; disturbed ventilation-perfusion ratio (VA/Q); alveolar hypoventilation; carbon dioxide (CO2) retention and increased respiratory airflow resistance; and changes in the respiratory mechanics of the rib cage and diaphragm, increasing respiratory muscle workload. 2,9,10 Respiratory muscle strength (RMS) can be measured by vacuum manometry and expressed as centimeters of water (cm H2 2 O) through maximal respiratory pressures (Pmax). 11,13 Maximal inspiratory pressure (PImax) is the highest negative pressure that can be generated during inspiration and refers to ventilatory capacity.…”
mentioning
confidence: 99%